Boosting Inflammation Resolution in Atherosclerosis: The Next Frontier for Therapy - Fredman, Gabrielle; Tabas, Ira (The American journal of pathology, 2017)
Defective inflammation resolution is the underlying cause of prevalent chronic inflammatory diseases, such as arthritis, asthma, cancer, and neurodegenerative and cardiovascular diseases. Inflammation resolution is governed by several endogenous factors, including fatty acid-derived specialized proresolving mediators and proteins, such as annexin A1. Specifically, specialized proresolving mediators comprise a family of mediators that include arachidonic acid-derived lipoxins, omega-3 fatty acid eicosapentaenoic acid-derived resolvins, docosahexaenoic acid-derived resolvins, protectins, and maresins. Emerging evidence indicates that imbalances between specialized proresolving mediators and proinflammatory mediators are associated with several prevalent human diseases, including atherosclerosis. Mechanisms that drive this imbalance remain largely unknown and will be discussed in this review. Furthermore, the concept of dysregulated inflammation resolution in atherosclerosis has been known for several decades. Recently, there has been an explosion of new work with regard to the therapeutic application of proresolving ligands in experimental atherosclerosis. Therefore, this review will highlight recent advances in our understanding of how inflammation resolution may become defective in atherosclerosis and the potential for proresolving therapeutics in atherosclerosis. Last, we offer insight for future implications of the field.